Propitious Selection - Hemenway, David (Quarterly Journal of Economics, 1990)
Journal Article Propitious Selection Get access David Hemenway David Hemenway Harvard School of Public Health Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 105, Issue 4, November 1990, Pages 1063–1069, https://doi.org/10.2307/2937886 Published: 01 November 1990